2020
DOI: 10.1038/s41598-020-73340-5
|View full text |Cite
|
Sign up to set email alerts
|

Ninjurin 1 dodecamer peptide containing the N-terminal adhesion motif (N-NAM) exerts proangiogenic effects in HUVECs and in the postischemic brain

Abstract: Nerve injury-induced protein 1 (Ninjurin 1, Ninj1) is a cell adhesion molecule responsible for cell-to-cell interactions between immune cells and endothelial cells. In our previous paper, we have shown that Ninj1 plays an important role in the infiltration of neutrophils in the postischemic brain and that the dodecamer peptide harboring the Ninj1 N-terminal adhesion motif (N-NAM, Pro26-Asn37) inhibits infiltration of neutrophils in the postischemic brain and confers robust neuroprotective and anti-inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Matsuki et al reported that Ninj1 is highly expressed in capillary pericytes (cPCs), is weakly expressed in ECs of the thoracic aorta, and could act as an anti-angiogenic regulator of cPCs in ischemic models [ 51 ]. Additionally, Yin et al showed that Ninj1 blockade enhanced penile angiogenesis in erectile dysfuntion [ 8 ] and Kim et al reported that dodecamer peptide Ninj1 promotes angiogenesis during strokes [ 9 ]. Compared to dysregulated angiogenesis in DR, these lesions differ in that vasoreparative processes are caused by ischemic injury and the main players are pericytes instead of macrophages [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsuki et al reported that Ninj1 is highly expressed in capillary pericytes (cPCs), is weakly expressed in ECs of the thoracic aorta, and could act as an anti-angiogenic regulator of cPCs in ischemic models [ 51 ]. Additionally, Yin et al showed that Ninj1 blockade enhanced penile angiogenesis in erectile dysfuntion [ 8 ] and Kim et al reported that dodecamer peptide Ninj1 promotes angiogenesis during strokes [ 9 ]. Compared to dysregulated angiogenesis in DR, these lesions differ in that vasoreparative processes are caused by ischemic injury and the main players are pericytes instead of macrophages [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inflammatory stimuli induce Ninj1 expression in leukocytes, enhancing adhesion to VECs and the extracellular matrix (ECM) and recruitment to the site of inflammation [ 6 ]. Various trials have been conducted to regulate the inflammation mediated by Ninj1-neutralizing antibodies, small interfering RNA (siRNA), peptides, and natural products [ 4 , 7 9 ]. However, a strategy to effectively regulate Ninj1 expression has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Ninjurin 1 (nerve injury-induced protein 1, or Ninj1) is a cell adhesion molecule responsible for cell–to–cell interactions between different cells and involved in many molecular pathways and processes (neuroinflammation, angiogenesis, muscle and osteoclasts development and others) [ 92 , 93 ]. Ninj1 is also involved in ECs\pericytes interaction and serves as a negative regulator of neovessel formation.…”
Section: Role Of Pericytes In Plaque Stabilisationmentioning
confidence: 99%
“…Further research found Ninj‐1 soluble form (soluble Ninj‐1, sNinj‐1) was increased in serum of atherosclerosis patient, and it was identified as an antiinflammatory mediator with the ability to ameliorate monocyte recruitment and development of atherosclerosis (Jeon et al, 2020). Moreover, another study demonstrated that the N‐terminal adhesion motif of Ninj‐1 exerted proangiogenic effects in HUVEC, contributing to its neuroprotective effects in the animal model of stroke (Kim et al, 2020).…”
Section: Role Of Pyroptosis In Atherosclerosismentioning
confidence: 99%